Evaluating Spending Policies in a Low-Return Environment. Issue 4 (1st September 2018) - Wang, Peng; Chapman, Laura; Peterson, Steven; Spinney, Jon
Abstract : For an endowment seeking to minimize payout variability while preserving the long-run health of the institution, appropriate spending policy is a crucial choice. We study two competing methods for setting spending policy—the "moving-average" method and the "snake-in-the-tunnel" (SIT) approach. We show that the SIT approach may significantly decrease the possibility of spending reductions in the short run. Additionally, the SIT approach with 3%–7% bands allows for a smooth evolution of payouts over time, which enhances spending predictability while preserving the endowment's real (inflation-adjusted) long-run purchasing power. Abstract : Disclosure: The authors report no conflicts of interest. Editor's Note Submitted 13 October 2017 Accepted 12 April 2018 by Stephen J. Brown